Developing E-Learning Media with the Contiguity Principle for the Subject of Autocad - Nur Hidayat; Samsul Hadi; Abd. Basith; Suwandi Suwandi (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Technological advances have made possible to reduce limitation of space and time in learning. Students can interact with teachers and other students indirectly without face to face meetings through e-learning media. To create effective e-learning media, factors to be mainly considered are multimedia learning principles, one of which is contiguity. Thus, this study was aimed at developing e-learning media with the contiguity principle and examining its quality. The media were tested for measuring its effectiveness by statistically analyzing the differences in students’ learning achievement and motivation. This study was research and development using quasi experimental techniques whose subject is Vocational High School also known as Sekolah Menengah Kejuruan Negeri 2 Yogyakarta. The result of this study was e-learning media with the contiguity principle. The feasibility evaluation showed that the product had good quality in the aspects of media and materials. The effectiveness testing showed insignificant differences in learning achievement and motivation between the students using e-learning media with the contiguity principle and without the contiguity principle with the scores of 0.325 and 0.873 respectively.